THE DIFFUSION AND ADOPTION OF GREEN REVOLUTION TECHNOLOGIES: LESSONS AND POLICY IMPLICATIONS FROM PIGEONPEA FARMERS IN KENYA - SIMTOWE, F.; MUANGE, E. (My University, 2013)
Significant advances have been made in generating high yielding varieties which are part of the so called Green revolution technologies. Raising hopes for a pulse green revolution, a number of improved varieties of pigeonpea have also been developed and released in Africa. The key motivation of this study is that, despite their perceived advantages in raising productivity, the diffusion and adoption of such varieties remains low We apply a quasi-experimental approach to data obtained from rural Kenya to assess the patterns of adoption of improved pigeonpea varieties and their determinants. The sample adoption rate of improved pigeonpea is found to be 36% while the potential adoption rate is estimated at 48%. The adoption gap resulting from the incomplete exposure to the improved pigeonpea is 12%. Adoption is found to be prominent among farmers with residences close to the agricultural offices, and among younger and wealthier farmers. The findings suggest that there is scope for increasing the adoption of improved pigeonpea, especially among young farmers once they are exposed to the new technologies and once the associated policy and technical constraints are addressed. JEL Codes:
Keywords: Pigeonpea